Body mass index, gender, and clinical outcome among hypertensive and diabetic patients with stage A/B heart failure. (23rd September 2013) - Ballo, Piercarlo; Betti, Irene; Barchielli, Alessandro; Castelli, Gabriele; De Luca, Leonardo; Gheorghiade, Mihai; Zuppiroli, Alfredo
Abstract : Objective: The existence of an "obesity paradox" in asymptomatic patients with preclinical heart failure (HF) has not been investigated. The prognostic value of BMI in a cohort of hypertensive and diabetic patients with stage A/B HF enrolled in the PROBE‐HF study was explored. Design and Methods: BMI was measured in 1003 asymptomatic subjects (age 66.4 ± 7.8 years, 48% males) with hypertension and/or type 2 diabetes and no clinical evidence of HF. Predefined endpoints were all‐cause mortality and a composite of death and hospitalization for cardiac causes. Results: During a follow‐up of 38.5 ± 4.1 months, 33 deaths were observed. Mortality in the normal BMI group (1.6 deaths per 100 patient‐years) did not differ to that in the overweight group (1.1 per 100 patient‐years, p = 0.31), but was higher than that in the obese group (0.4 per 100 patient‐years, p = 0.0089). In multivariable analysis, obesity (hazard ratio [HR] 0.27 [0.09‐0.85], p = 0.025) but not overweight (HR 0.68 [0.32‐1.45], p = 0.32) was associated with lower risk of death. Obesity was also independently associated with reduced risk of the composite endpoint (HR 0.54 [0.28‐0.99], p = 0.047). Conclusion: In asymptomatic hypertensive and diabetic patients with preclinical HF, obesity is associated with better survival and reduced risk of events.